Archipreneur – The Future of Architecture - Syed Fadzil, Sharifah Fairuz (MAJ - Malaysia Architectural Journal, 2021)
Architect, according to most definitions and dictionaries, is a person who designs buildings, and in most cases also supervises their construction. Architects ensure buildings are built correctly according to the design specifications. Buildings designed are not only pleasant looking in their aesthetic values, but more importantly they should be safe for use. On site, an architect is known as the superintendent officer or the S.O. whereby he coordinates building construction and works amongst the contractor and the consultant engineers and surveyors. The architect is a professional. By virtue he / she must have completed a required course of studies at the university and practice with competence. This can usually be measured against an established set of standards or examinations set by their professional bodies. A person responsible for achieving a particular plan or aim: is also sometimes known as an architect. Tun M, for example, is often described as the architect for Malaysia’s development and progress in the 1980’s. Architect can also mastermind a system or a process. There are software architects for computer systems, and architects in some planning and technology. Architecture is the course one should take to become an architect. It usually takes between 5 – 6 years at the university for this. Architecture is the art or practice of designing and constructing buildings – so they will look nice on the outside and feels good from the inside.